Solving the “Colomerus vitis conundrum”: genetic evidence reveals a complex of highly diverged groups with little morphological differentiation - Maboeei, Palesa (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.